Investigation of liquid-crystalline behavior of nickel octakisalkylthiophthalocyanines and orientation of their films - Basova, TV; Gürek, AG; Ahsen, V (Elsevier, 2002)
In this work, the mesogenic properties of octa-alkyl-substituted Ni(II) phthalocyanine derivatives are reported. These phthalocyanines (Pc) demonstrate thermotropic phase behavior and give rise to discotic liquid crystals. The dependence of film orientation on temperature in the temperature range from 0 to 300 degreesC was studied by the method of Raman spectroscopy. It was shown that the films are disordered in the temperature range where the samples of NiPc are solid. Oriented films may be obtained by annealing at the temperatures at which the materials are mesogenic. According to results from a Raman polarization study, the phthalocyanine molecules in this ordered films are oriented virtually perpendicular to the substrate surface. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: phthalocyanine; discotic liquid crystal; thin film; Raman spectra